Discovering the effect of solvents on poly(2-aminoethyl methacrylate) grafting onto chitosan for an in vitro skin model. (1st November 2022) - González-Torres, Maykel; Vargas-Muñoz, Susana; Leyva-Gómez, Gerardo; Méndez-Padilla, Ma. Guadalupe; Cortés, Hernán; Nuñez-Rojas, Edgar; González-Mendoza, Oswaldo; Pérez-Díaz, Mario Alberto; Ruvalcaba-Paredes, Erika Karina; Lima, Enrique; Brena, Ana María; Rodríguez-Talavera, Rogelio; et al.
Abstract: The design of controlled grafting copolymers is critical in synthesizing effective artificial cellular matrices because of their regulatory role in cellular behavior. However, it is unclear whether poly(2-aminoethyl methacrylate) grafted onto chitosan generated by gamma-radiation-induced graft polymerization in different solvents can influence the physicochemical properties and biotech applicability of the copolymer. This work aims to demonstrate for the first time the effect of various solvents on the synthesis, properties, and biological performance of grafted chitosan using the simultaneous irradiation method. The results proved that the solvent is one of the critical factors affecting the properties of the modified polysaccharide. The degree of grafting showed a solvent-dependent profile. Hexane presented utmost importance concerning the degree of grafting. Ethyl acetate showed the best results in grafting extent and human dermal fibroblast growth. These findings indicate that proper solvent selection determines the possible copolymer use for in vitro engineered skin substitute models. Graphical abstract: Unlabelled Image Highlights: The effect of solvent on CS-g-PAEMA synthesis and performance was investigated. The degree of grafting and grafting extent showed a solvent-dependent profile. The choice of the solvent also influenced the in vitro HDFs grown in the copolymer. Hexane presented utmost importance concerning the degree of grafting dependence. Ethyl acetate showed maximum graft extent, cell growth, and proliferation results.